Hubungan antara dukungan sosial dengan resiliensi akademik pada Mahasiswa rantau yang sedang mengerjakan skripsi - Astri Ardiyanti Said; Agustin Rahmawati; Dellawaty Supraba (Jurnal Psikologi Tabularasa, 2021)
Academically resilient students are students who are able to effectively deal with four conditions wich are, setback, challenges, adversity, and pressure in the academic context. This study aims to determine whether there is a relationship between social support and academic resilience of overseas students who are working on thesis. The subjects in this study were students part of Maluku Utara – Malang Student Association (IPMA - MUM) who were working on thesis, with 72 students. The sampling technique in this study is saturated sample. This research method uses quantitative research by collecting data using the scale of academic resilience and social support scale with the likert model. In order to obtain the results of hypothesis testing with a correlation index of 0.469 with a significant level of 0.000 so that the results of this study indicate a positive correlation which means the higher social support that individuals get, the higher the academic resilience and vice versa.